Analisa Kelayakan Pelebaran Jalan Bringkang-Menganti Kabupaten Gresik - Annisa Shibyan, Nadya; Ayunaning, Kholidia (Jurnal Teknik Sipil dan Lingkungan, 2025)
This study analyzes the proposed widening of the Bringkang–Menganti Road to evaluate its impacts on traffic performance and economic feasibility. Under existing conditions, the 2/2 undivided road has a capacity of 2,660 pcu/h with a degree of saturation (DS) of 0.780, which is projected to increase to 1.034 by 2030. After widening to a 4/2 undivided road, capacity increases to 5,505.28 pcu/h and DS decreases to 0.377, accompanied by higher vehicle speeds. From an economic perspective, vehicle operating cost savings amount to IDR 776.17 million, while travel time savings reach IDR 16.54 billion, resulting in total economic benefits of IDR 17.31 billion. However, the feasibility analysis yields a BCR of 0.91 and an NPV of –IDR 3.12 billion at a 5.25% discount rate. Therefore, although the road widening improves traffic performance, the project is not economically feasible within the 2025–2029 analysis period.